Optimization of angular distortion on weld joints using taguchi approach - Arifin, Amir; Gunawan,; Mataram, Agung; Yani, Irsyadi; Pratiwi, Diah Kusuma; Muhammad Yanis,; Sani, Khoirul Anwar (Penerbit Universiti Kebangsaan Malaysia, 2019)
Welding process is joining method which is extensively utilized in shipbuilding and automotive industry. Distortion is a classic problem encountered during the welding process which always occurs in welding processes. Distortion on weld joint involves many parameters that influence such as properties of materials and welding parameters. The objective of this work is to investigate effect of various processes of Shielded Metal Arc Welding (SMAW) on angular distortion in low carbon steel weld joints. To obtain optimum parameters of angular distortion, the effect various welding parameter is analysed using Taguchi Method. In this work, the effect of groove type, welding current and root opening are investigated for determining angular distortion. Taguchi method with L9 orthogonal array is utilized to analysed contribution for each parameter. ANOVA results revealed that the welding current the significant contribution parameter, on the other hand root opening shows minimum contribution to determine angular distortion value. Optimum parameter is obtained with groove type, welding current and root opening is X, 75A and 3 mm, respectively. Welding current parameter is considered the most significant contribution to determine for angular distortion effect due to has the highest contribution (50.04 %) than the other parameters groove type and root opening, with contribution value 21.76 %, 2.38%, respectively. Moreover, hardness test result on weld joint shows that X type groove has maximum hardness number than the other groove type.